2005
DOI: 10.1074/mcp.m500055-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Studying Lung Cancer-related Proteins in Human Blood

Abstract: Early stage lung cancer detection is the first step toward successful clinical therapy and increased patient survival. Clinicians monitor cancer progression by profiling tumor cell proteins in the blood plasma of afflicted patients. Blood plasma, however, is a difficult cancer protein assessment medium because it is rich in albumins and heterogeneous protein species. We report herein a method to detect the proteins released into the circulatory system by tumor cells. Initially we analyzed the protein component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 29 publications
2
93
0
1
Order By: Relevance
“…Through our method, we successfully identified proteins that are putative or currently used as biomarkers of lung cancer, including CEA (27,28), pro-GRP (29,31), SCC antigen (47,48), tumor M2-PK (49), NCAM (35)(36)(37), chromogranin A (29), and chromogranin B (30). In addition, we identified putative markers previously reported in lung-related proteomics studies such as member C1 of aldo-keto reductase family 1 identified by Huang et al (25) as dihydrodiol dehydrogenase and matrix metallopeptidase 1 found to be overexpressed in lung cancer patients and especially in late stage (18). Furthermore, 129 of 291 extracellular and 168 of 415 membranous proteins identified in this study were found in the plasma proteome.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Through our method, we successfully identified proteins that are putative or currently used as biomarkers of lung cancer, including CEA (27,28), pro-GRP (29,31), SCC antigen (47,48), tumor M2-PK (49), NCAM (35)(36)(37), chromogranin A (29), and chromogranin B (30). In addition, we identified putative markers previously reported in lung-related proteomics studies such as member C1 of aldo-keto reductase family 1 identified by Huang et al (25) as dihydrodiol dehydrogenase and matrix metallopeptidase 1 found to be overexpressed in lung cancer patients and especially in late stage (18). Furthermore, 129 of 291 extracellular and 168 of 415 membranous proteins identified in this study were found in the plasma proteome.…”
Section: Discussionmentioning
confidence: 72%
“…Then, we performed literature searches to ensure that these proteins have not been examined as serological markers for lung cancer and showed biological connections with lung or other cancers. We also compared selected proteins with the proteomes of lung-related diseases (lung cancer (18,25,26) and pleural effusion (11)) or the proteome of a lung-related biological fluid (induced sputum (9, 10)) and serum (Plasma Proteome Database). Finally, potential candidates that had commercially available antibodies or immunoassays were selected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29] Additionally, high-output proteomics studies revealed that Ig chain fragments were elevated in cancer patients compared with normal healthy controls. [30][31][32] The elevated serum antibody levels were thought to be produced from autoimmune reactions that were stimulated by the disordered immune system. 25,29 Based on our findings, some of these Ig chains could be inferred to arise from the cancer cell itself.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the discrepancy between immortalized cancer cells and clinical samples may be considerable. Therefore, we previously developed a novel approach based on the primary culture of tumor tissues and proteomic analysis of serum-free CM [11,12]. In this study, we collected serum-free CM from cultures of cancerous and surrounding noncancerous tissues from six HCC patients with HBV infection.…”
mentioning
confidence: 99%